Framing Analysis on Covid -19 Vaccination Boycott News on suara.com and kompas.com - Putri Amira; Daniel Susilo (Jurnal Spektrum Komunikasi, 2023)
News about the COVID-19 vaccine has raised doubts among society, thus forming a COVID-19 vaccine rejection group. The rejection of the COVID-19 vaccine resulted in a negative portrayal of the COVID-19 vaccine refusers in mass media. This study uses the Zhongdang Pan and Gerald M. Kosicki framing analysis method which is expected to be able to describe the framing of the issue of rejection of the COVID-19 vaccine by Kompas.com and Suara.com. The results of this study indicate that the two media frame the issue of imposing fines and terminating social security for those who refuse to vaccinate against COVID-19 as imposing citizens' rights and threatening people's freedoms. The conclusion of this study is that the framing of Kompas.com and Suara.com news is influenced by several things, namely the positioning of journalists, the use of news sources, and the use of words in describing an event.